Memahami Tujuan Pembelajaran dan Imlementasinya dalam Pengembangan Kurikulum MI - Khumaimah, Rinatul (Institut Agama Islam Al-Hikmah Tuban, 2023)
Abstract, The task of teachers in an effort to achieve learning success is to formulate learning objectives appropriately. Not all teachers have competence in formulating indicators. This study aims to provide information about the importance of understanding learning objectives and their implementation in curriculum development in MI. The research method used is literature research, where researchers obtain data through literature studies or literature without going into the field. The results showed that in a learning process teachers need to consider several things before learning begins in order to achieve the expected learning objectives. So far, many teachers in MI have formulated learning objectives without paying attention to the correct way of preparation. One of them is the application of operational verbs (KKO) in learning objectives. According to Anderson's version, revising Bloom's description, there are three domains in Education, namely cognitive, psychomotor and affective aspects. In the cognitive aspect there are 6 taxonomic levels, the psychomotor aspect is 5 levels and the affective aspect is 5 levels. At each level there are operational verbs that become teacher references in formulating learning objectives. Keywords: Learning Objectives, MI Teachers, Curriculum Development